2012
DOI: 10.1038/jhh.2012.37
|View full text |Cite
|
Sign up to set email alerts
|

The association between apolipoprotein E gene polymorphisms and essential hypertension: a meta-analysis of 45 studies including 13 940 cases and 16 364 controls

Abstract: The apolipoprotein E single-nucleotide polymorphisms are among the potential candidate genes that may serve as modulators in susceptibility to essential hypertension. In an effort to clarify earlier inconclusive results, we performed a meta-analysis of population-based case-control genetic association studies. Random-effects methods were applied on summary data in order to combine the results of the individual studies. We identified in total 45 studies, including 13 940 hypertensive cases and 16 364 controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 63 publications
0
13
0
4
Order By: Relevance
“…A meta-analysis of 45 studies including 13 940 cases and 16 364 controls by Stoumpos et al indicated an increased risk of hypertension associated with the ε4 allele compared with the ε2 and ε3 alleles [33]. This association was stronger in populations of Asian descent, with an odds ratio (OR) of 1.49 (95% confidence interval (CI): 1.05–2.13) vs an OR of 1.39 (95% CI: 1.12–1.72) for the overall population (mostly of European descent).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 45 studies including 13 940 cases and 16 364 controls by Stoumpos et al indicated an increased risk of hypertension associated with the ε4 allele compared with the ε2 and ε3 alleles [33]. This association was stronger in populations of Asian descent, with an odds ratio (OR) of 1.49 (95% confidence interval (CI): 1.05–2.13) vs an OR of 1.39 (95% CI: 1.12–1.72) for the overall population (mostly of European descent).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis included 29 studies involving 2,737 CI cases and 2,689 controls suggested that APOE E4 allele was associated with an increased risk of developing cerebral infarction in Chinese population [36]. A meta-analysis of 45 studies including 13,940 cases and 16,364 controls found that APOE gene polymorphisms were associated with essential hypertension [37]. A meta-analysis of 28 case–control studies provided evidence for an association between the APOE E4 allele and frontotemporal lobar degeneration [38].…”
Section: Discussionmentioning
confidence: 99%
“…The ε 4 allele of the gene that codes apolipoprotein E (APOE) has been consistently found to be a risk factor for Alzheimer's disease (AD) and other cognitive disorders . APOE‐ ε 4 may also be associated with poor cognitive performance in older adults without dementia and is associated with hypertension, which in turn may increase the risk of cognitive impairment . Prior studies suggest that hypertension and APOE have a cumulative effect on the risk of AD, but fewer studies have explored the combined effect on cognition in older adults without dementia.…”
mentioning
confidence: 99%
“…1 APOE-e4 may also be associated with poor cognitive performance in older adults without dementia 2,3 and is associated with hypertension, which in turn may increase the risk of cognitive impairment. 4,5 Prior studies suggest that hypertension and APOE have a cumulative effect on the risk of AD, 6 but fewer studies have explored the combined effect on cognition in older adults without dementia. For example in the Honolulu-Asia Aging Study, midlife high systolic blood pressure had a stronger negative effect on global measures of cognition in participants with APOE-e4.…”
mentioning
confidence: 99%